A Rapid Evidence Assessment of the effectiveness of educational interventions to support children and young people with multi-sensory impairment. - Ellis, L; Douglas, G; Hewett, R; McLinden, T; Terlektsi, E; Wotten, AM; Ware, J; Williams, L (Welsh Government, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:5DZTY8BD 2405685:2FIF7LND

The private schooling phenomenon in India: A review - Kingdon, Geeta Gandhi (2019)
This paper examines the size, growth, salaries, fee levels and per-pupil-costs of private schools, and compares these with the government school sector. Official data show a steep growth of private schooling and a corresponding rapid shrinkage in the size of the government school sector in India, suggesting parental abandonment of government schools. Data show that a very large majority of private schools in most states are ‘low-fee’ when judged in relation to: state per capita income, perpupil expenditure in the government schools, and the officially-stipulated rural minimum wage rate for daily-wage-labour. This suggests that affordability is an important factor behind the migration towards and growth of private schools. The main reason for the very low fee levels in private schools is their lower teacher salaries, which the data show to be a small fraction of the salaries paid in government schools; this is possible because private schools pay the market-clearing wage, which is depressed by a large supply of unemployed graduates in the country, whereas government schools pay bureaucratically determined minimum-wages. The paper shows how education policies can be harmful when formulated without seeking the evidence.
KerkoCite.ItemAlsoKnownAs: 2339240:Q358PXQL 2405685:BBJ3G7H2
Keywords: ⛔ No DOI found

A cognitive assessment tool designed for data collection in the field in low-and middle-income countries - Ford, Cassie B.; Kim, Ha Yeon; Brown, Lindsay; Aber, J. Lawrence; Sheridan, Margaret A. (Research in Comparative and International Education, 2019)
The Rapid Assessment of Cognitive and Emotional Regulation (RACER) is a tablet-based assessment tool for children that measures executive function (EF) skills. Instructions that are brief and visually presented; game-like tasks are designed to easily engage children regardless of literacy level and variable test administration settings. RACER measures inhibitory control and working memory. This study presents the theoretical rationale and empirical evidence for tablet-based assessments of EF, the process of administering the RACER assessments. The current sample consists of students in Lebanon (N=1900) and Niger (N=850). The results indicate that individual differences in EF can be assessed by the RACER tablet tasks. Specifically, we demonstrate that EF scores are associated in expected ways with age and that tasks function similarly to what has been observed in high-income countries. The feasibility and utility for researchers, practitioners, and clinicians, of this cognitive assessment tool is discussed.
shortDOI: 10/ggcdmq KerkoCite.ItemAlsoKnownAs: 10.1177/1745499919829217 10/ggcdmq 2339240:LIPC5YY2 2339240:TL333DE5 2339240:XVBLDC46 2339240:Z5BEQNRN 2405685:3PXAARND 2405685:JSZ4DA4J 2405685:K8AE89HH

Complexity and Considerations in Delivering Adaptive Learning Digital Services - Proctor, Jamie (EdTech Hub, 2019)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4561896 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4561896 2339240:M4PBAXK6 2405685:XU7B7DHZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH